Neoproterozoic tectonic and magmatic episodes in the NW sector of Borborema Province, NE Brazil, during assembly of Western Gondwana - Santos, Ticiano J. Saraiva dos; Fetter, Allen H.; Hackspacher, Peter Christian [UNESP]; Van Schmus, W. R.; Neto, J. A. Nogueira (Pergamon-Elsevier B.V. Ltd, 2008)
The Medio Coreau domain of NE Brazil is located along the northwest margin of Borborema Province, the western branch of a Brasiliano/Pan-African collisional belt that formed during the assembly of Western Gondwana. The early Paleoproterozoic basement of the Medio Coreau domain is composed of migmatitic gneisses and juvenile granulites, overlain by late Paleoproterozoic and Neoproterozoic rocks intruded by syn- to post-tectonic Brasiliano granitoids. According to integrated structural and geochronological data (U-Pb zircon and monazite ages), the Neoproterozoic tectonic evolution of the Medio Coreau is characterized by low-angle thrusting and transcurrent deformation. U-Pb geochronological data from plutons intruded during this compressional regime indicate the collisional evolution began at approximately 622 Ma and continued until about 591 Ma. The continuation of convergence until approximately 560 Ma resulted in the formation of NE-SW and E-W shear zones within the Borborema Province and adjoining West African provinces. The final stage of the ductile tectonism was characterized by uplift and high-angle fault generation between approximately 560 and 545 Ma. The last tectonic event was an extensional phase, resulting in the formation of the Jaibaras graben and intrusion of post-orogenic granites at around 532 Ma. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Borborema Province; Medio Coreau domain; tectonic evolution; Western Gondwana